Culture, Emotion Socialization and Children's Inhibitory Control. Issue 5 (20th October 2022) - Doan, Stacey N.; Song, Qingfang
ABSTRACT: In the current study, we investigated the relations among maternal emotion socialization practices and children's inhibitory control (IC) performance in Chinese and European American families. Fifty-three Chinese ( M age = 60 months) and 52 European American ( M age = 50 months) children and their mothers participated in this study. Maternal emotion socialization was assessed using mothers' reported reactions to children's negative emotions by completing the Coping with Children's Negative Emotions Scale (CCNES). Child IC was assessed through two observational measures. Results revealed significant group differences. Specifically, Chinese mothers adopted more harsh responses and less distress responses as compared to European American mothers. Chinese children scored higher on IC than did European American children. Moderation analyses also suggest that maternal harsh responses and distress responses were negatively related to children's IC performance for European American group but not for Chinese group.